Transcriptional control of endothelial cell development. - De Val, S; Black, B (2009)
The transcription factors that regulate endothelial cell development have been a focus of active research for several years, and many players in the endothelial transcriptional program have been identified. This review discusses the function of several major regulators of endothelial transcription, including members of the Sox, Ets, Forkhead, GATA, and Kruppel-like families. This review also highlights recent developments aimed at unraveling the combinatorial mechanisms and transcription factor interactions that regulate endothelial cell specification and differentiation during vasculogenesis and angiogenesis.